Determination of Gestational Age and Observation of Kacang Goat Fetal Development during 60 Days of Pregnancy by Using Transcutaneous Ultrasonography - Sayuti, Arman; Khairiah, Khairiah; Siregar, Tongku Nizwan; Melia, Juli; Syafruddin, Syafruddin; Rahmi, Erdiansyah; Herrialfian, Herrialfian; Abrar, Mahdi; Panjaitan, Budianto; Daud, Razali (Jurnal Veteriner, 2019)
This study was aimed to observe correlation between gestational age and fetal growth of Kacang goat for 60 days after mating with transcutaneous ultrasonography visualization. Three female goats of productive age with normal estrus cycle and one male goat were used in this study. The female goats were synchronized with double injection of prostaglandin F2á (PGF2á)  intramuscularly with dosage of 1 mL for each female goat with 11 days’ time interval. Observation of oestrus was conducted using male goat after being synchronized. When the sign of estrus were prominent, the female goats were naturally mated. The result was pregnant positive for one female goat. Detection of early pregnancy was observed on the 24th days after mating, with the result of 6.77 mm length embryo by isoechogenic visualization. On 35th days of pregnancy, fetal could be seen clearly in isoechogenic to hyperechogenic visualization with head diameter and fetal length were 17.4 mm and 36.2 mm, consecutively. The observation also found the placentom. On day 45 of pregnancy, head diameter and fetal length were 21.8 mm and 40.6 mm. Later on day 49 of pregnancy, the size of gestational saccus was 44.1 mm, with head diameter of 25 mm, and average placentom diameter size of 12.4 mm. On day 53 of pregnancy, head diameter was 25.2 mm with fetal length of 63.6 mm and placentom diameter of 15 mm. On day 56 of pregnancy, vertebrae of fetal were observed using hyperechogenic visualization and placentom was measured 17.9 mm in diameter. On day 60 of pregnancy, we observed that the fetal length was 79.8 mm and the organs such as eyes, heart, liver, os costae, and fetal extremities, could be observed clearly. The size of developing fetal and organs would grow along with the addition of gestational age.